Bioconversion of plant biomass hydrolysate into bioplastic (polyhydroxyalkanoates) using Ralstonia eutropha 5119. (January 2019) - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Tae-Rim; Jung, Hye-Rim; Yang, Soo-Yeon; Moon, Yu-Mi; Song, Hun-Suk; Jeon, Jong-Min; Choi, Kwon-Young; Yang, Yung-Hun
Graphical abstract: Highlights: Ralstonia eutropha 5119 can co-metabolize biomass derived byproducts with glucose. Furfural, hydroxymethylfurfural and acetate promote biomass and PHA production. Vanillin is more toxic followed by furfural > hydroxymethylfurfural > acetate. Miscanthus biomass hydrolysate resulted in high PHA (Yp/s, 0.14 g/g) yield. PHA produced from biomass hydrolysate has similar properties to P(3HB- co -3HV). Abstract: Pretreatment of lignocellulosic biomass results in the formation of byproducts (furfural, hydroxymethylfurfural [HMF], vanillin, acetate etc.), which affect microbial growth and productivity. Furfural (0.02%), HMF (0.04%), and acetate (0.6%) showed positive effects on Ralstonia eutropha 5119 growth and polyhydroxyalkanoate (PHA) production, while vanillin exhibited negative effects. Response optimization and interaction studies between the variables glucose, ammonium chloride, furfural, HMF, and acetate using the response surface methodology resulted in maximum PHA production (2.1 g/L) at optimal variable values of 15.3 g/L, 0.43 g/L, 0.04 g/L, 0.05 g/L, and 2.34 g/L, respectively. Different lignocellulosic biomass hydrolysates (LBHs), including barley biomass hydrolysate (BBH), Miscanthus biomass hydrolysate (MBH), and pine biomass hydrolysate (PBH), were evaluated as potential carbon sources for R. eutropha 5119 and resulted in 1.8, 2.0, and 1.7 g/L PHA production, respectively. MBH proved the best carbon source, resulted in higher biomass (Yx/s, 0.31 g/g) and PHA (Yp/s, 0.14 g/g) yield.